ProteotoxomiRs: Diagnostic and pathologic miRNA signatures for reductive stress induced proteotoxic heart disease - Santhosh Kumar Karthikeyan; Palanisamy Nallasamy; Jarrell Matthew Cleveland; Ahila Arulmani; Ashvanthi Raveendran; Mariam Karimi; Mohammad Owais Ansari; Anil Kumar Challa; Moorthy P. Ponnusamy; Ivor J. Benjamin; Sooryanarayana Varambally; Namakkal S. Rajasekaran (Redox Biology)
Proteotoxic stress progressively leads to irreversible cardiac abnormalities. Using a mouse model of reductive stress-induced proteotoxic cardiomyopathy, we identified novel microRNA signatures, termed “ProteotoxomiRs,” which reflect stage-specific and transgene-specific responses to proteotoxic stress. Seven microRNAs were uniquely linked to the human mutant R120G-αB-Crystallin transgene, indicating their direct association with the pathogenic protein. Additionally, we uncovered two distinct microRNA profiles associated with the early (pre-onset) and late (cardiomyopathy/heart failure) stages of disease progression. Early-stage signatures primarily modulate signaling pathways essential for cardiac health, including mTOR and MAPK, while late-stage signatures reveal regulatory disruptions in calcium signaling and autophagy insufficiency, driving irreversible cardiac damage caused by reductive stress (RS) and proteotoxicity in transgenic mice. These findings reveal stage-specific miRNA biomarkers with potential diagnostic and prognostic value, offering new insights into the molecular underpinnings of proteotoxic cardiac disease. Moreover, our miRNA-mRNA interaction analysis uncovered potential targets unique to the transgene-specific, early, and late stages of the disease, including several promising druggable candidates, warranting further validation for translational applications.